HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN PSYCHOLOGICAL WELL-BEING PADA KAUM HOMOSEKSUAL DI KOTA MEDAN - Hendrick Hendrick (Psikologi Prima, 2020)
AbstractThis study aims to find out relationship between social support and psychological well-being on homosexuals at Medan city. The hypothesis proposed in this study states that there is a positive relationship between social support and psychological well-being, with the assumption that the higher social support, the higher will the psychological well-being be and conversely the lower the social support, the lower will psychological well–being be. The subjects of this study were 95 person of homosexuals at Medan city which were selected by total population sampling method. Data were obtained from a scale to measure social support and psychological well-being. The calculation was performed by means of testing requirements analysis (assumption), which consists of normality test for distribution and linearity test for relationship. The analysis of the data is Product Moment Correlation with SPSS 20 for Windows. The results of data analysis showed that the correlation coefficient was 0,438 with p 0,000 (p <0,05). It shows that there is a positive relationship between social support and psychological well-being. These results indicate that the contribution of a given variable of social support on the psychological well-being was 19,2 percent, while the remaining 80,8 percent is influenced by other factors not examined. From the results it is concluded that the hypothesis stating that there is a positive relationship between social support with the psychological well-being is acceptable.